Penyakit pada Tanaman Buncis (Phaseolus vulgaris) beserta Teknik Pengendaliannya di CV. Reja Mayur : Diseases of Bean Plants (Phaseolus vulgaris) and Control Techniques in CV. Reja Mayur - Frida Nur Aisah; Yenny Wuryandari (Agrocentrum, 2023)
Beans (Phaseolus vulgaris) are widely cultivated by farmers in several regions in Indonesia, one of which is in CV. Reja Mayur Pacet, Mojokerto. Beans (Phaseolus vulgaris) is a type of legume that is usually used as a cooking ingredient.Obstacles that are often experienced in the cultivation process cause the quantity and quality of production to decrease, namely the attack of disease-causing pathogens on plants. The study was conducted in November-December 2022. The research used observation methods, literature studies, active participation, and interviews. The data collected are the type of disease in chickpea plants, symptoms of the disease, and the technique of controlling the disease. The results of the study found that there are 3 types of diseases that attack chickpea plants in CV. Reja Mayur, namely leaf rust, anthracnose, and mosaic. Some of the control techniques applied are the use of PGPR, crop rotation, mechanical control, and the use of vegetable pesticides.